Boosting productivity through lean manufacturing efficiency in furniture Small and Medium Enterprises (SMEs) - Febianti, Evi; Muharni, Yusraini; Ramdhani, Desi; Anggraeni, Shanti Kirana (Journal Industrial Servicess, 2024)
A furniture manufacturer, a Small and Medium Enterprise (SME) whose main product is wooden chairs, has experienced problems in its manufacturing process. There are products that do not meet the desired size. The purpose of this research is to identify the most dominant waste through Borda weight calculations, determine the tools used in Value Stream Analysis Tools (VALSAT), find the root causes of the problems, and provide improvement suggestions using a fishbone diagram, as well as prioritize improvement suggestions using the Analytic Hierarchy Process (AHP). The research results using Borda weighting found that the most dominant waste was defect waste with a weight of 0.29. The VALSAT tool selected was Process Activity Mapping (PAM) with a score of 5.94. Improvement suggestions based on the fishbone diagram include work supervision, scheduling equipment and machinery maintenance, raw material checks, the creation of standard operating procedures (SOPs), and human resources training. The improvement suggestion prioritized based on the AHP results was the creation of standard operating procedures (SOPs) with a weight of 0.500. The difference in Process Cycle Efficiency increased from the previous 71% to 76% after the improvements.